Vestibular function in children with cochlear implant: Impact and evaluation - Deng, Jianhang; Zhu, Qianchen; Zhang, Kangjia; Xie, Dinghua; Wu, Weijing (Frontiers in Neurology, 2022)
Over the last 30 years, cochlear implant (CI) has been dedicated to improving the rehabilitation of hearing impairments. However, CI has shown potential detrimental effects on vestibular function. For children, due to atypical symptoms and difficulty in cooperating with vestibular function tests, systematic and objective assessments of vestibular function with CI have been conducted sparsely. This review focuses on the impact of vestibular function in children with CI and summarized the evaluation of vestibular function in children. In addition, some recommended strategies are summarized and proposed.